Rare earth phosphate aluminum oxide composite material for emission control catalyst and preparation method of rare earth phosphate aluminum oxide composite material

By using a composite material of transition alumina-based material and rare earth phosphate in the emission control catalyst, the problem of rhodium inactivation on the alumina support is solved, the thermal stability and activity of the catalyst are improved, and stricter emission control requirements are met.

CN120155200APending Publication Date: 2025-06-17SASOL GERMANY GMBH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510328432.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2018-02-21
Filing Date
2019-02-20
Publication Date
2025-06-17

AI Technical Summary

Technical Problem

In the existing emission control catalysts, the problem of rhodium inactivation on the alumina support leads to a reduction in catalytic activity and it is difficult to meet the stricter thermal stress requirements.

Method used

A composite material of transition alumina-based material and rare earth phosphate is used as a catalyst support. The rare earth phosphate has a microcrystal size of less than 50 nm after calcination at 1000°C to ensure that it is uniformly dispersed in the transition alumina matrix.

Benefits of technology

It improves the thermal stability and catalytic activity of rhodium, enhances the thermal stress capability of the catalyst, and meets stricter emission control requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120155200A_ABST
    Figure CN120155200A_ABST
Patent Text Reader

Abstract

The invention discloses a rare earth phosphate aluminum oxide composite material for emission control catalysts and a preparation method of the rare earth phosphate aluminum oxide composite material. The present invention specifically relates to a composition for a catalyst system in an emission control system comprising a transition alumina-based material and a rare earth phosphate, and to a method of preparing the same.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of Chinese Patent Application No. 201980011208.4, titled "Rare Earth Phosphate Alumina Composite Material for Emission Control Catalyst and Its Preparation Method", with an application date of February 20, 2019. Technical Field

[0002] The present invention relates to a composition for a catalyst system in an emission control system, the composition comprising a transition alumina-based material and a rare earth phosphate, and to a method for its preparation. Background Art

[0003] In the prior art, in emission control catalysts, three-way catalyst systems (hereinafter referred to as "TWC") include noble metals such as platinum (Pt), palladium (Pd) or rhodium (Rh), carriers such as alumina, cerium dioxide, zirconia, cerium dioxide-zirconia composite oxides, and a catalyst support (carrier, substrate, support) made of a ceramic or metal material. In these TWC systems, rhodium acts as a very important active component, mainly used to convert harmful NO x into N2. It is well known that rhodium supported on alumina tends to be inactivated by an irreversible reaction with Al2O3 under lean conditions, forming catalytically inactive rhodium aluminate. Therefore, it is necessary to enhance the thermal stability of the supported rhodium. Thermal stability (or thermostability) refers to the ability of a substance to resist irreversible changes in its chemical and / or physical structure, for example, at relatively high temperatures, by resisting one or more of decomposition, sintering, chemical change or phase transformation.

[0004] The prior art has provided various solutions, such as using ZrO2 as a support material for rhodium. However, due to more stringent regulations and more challenging thermal stress requirements, there is a need for an improved support for rhodium-based washcoats. M. Machida et al.: "Tuning the Electron Density of Rh Supported on Metal Phosphates for Three-Way Catalysis", J. Phys. Chem. C 2015, 119, 11653 - 11661 proposed an improvement, which described the use of rare earth phosphates as support materials for rhodium in TWC. However, the problem with using these bulk rare earth phosphates as supports is that rhodium cannot be well dispersed on the support.

[0005] Therefore, there is a need to improve these systems. Summary of the Invention

[0006] According to one aspect of the present invention, there is provided a composition for use as a support in a catalyst system, comprising:

[0007] i) a transition alumina-based material; and

[0008] ii) a rare earth phosphate, characterized in that after calcination at 1000 °C for 3 hours, its crystallite size is less than 50 nm, preferably less than 15 nm, and most preferably less than 10 nm.

[0009] Transition alumina refers to all aluminas in the transition state between boehmite and α-alumina.

[0010] According to another aspect of the present invention, there is provided a method for preparing the above composition for use as a support in a catalyst system, the method comprising:

[0011] i) providing a transition alumina rare earth oxide material, wherein the transition alumina rare earth oxide material is prepared by a method comprising the following steps:

[0012] a) preparing a suspension comprising a transition alumina precursor;

[0013] b) preparing an aqueous solution of a rare earth salt (rare earth salt solution);

[0014] c) combining the suspension with the rare earth salt solution to form an alumina rare earth salt mixture;

[0015] d) drying the alumina rare earth salt mixture to form a dried alumina rare earth salt mixture; and

[0016] e) calcining the dried alumina rare earth oxide salt mixture to form the transition alumina rare

[0017] earth oxide material;

[0018] ii) impregnating the transition alumina rare earth oxide material with an aqueous solution comprising phosphate ions to form an impregnated transition alumina rare earth oxide material; and

[0019] iii) calcining the impregnated transition alumina rare earth oxide material. Detailed Description

[0020] The composition comprises a transition alumina-based material and a rare earth phosphate.

[0021] Transition alumina-based materials include transition alumina, and most preferably transition alumina derived from boehmite, transition alumina derived from silica-alumina, transition alumina derived from doped alumina, or transition alumina derived from mixtures thereof. Doped alumina refers to alumina doped with alkaline earth metal oxides, ZrO2, rare earth oxides, or TiO2, each in the range of 0.1 wt.% to 20 wt.%, preferably 1 wt.% to 5 wt.%, or alumina doped with mixtures thereof. The transition alumina-based material is preferably transition alumina derived from boehmite.

[0022] Transition alumina refers to all aluminas in a transition state between boehmite and α-alumina.

[0023] According to one embodiment of the present invention, the composition comprises at least 50 wt.% of a transition alumina-based material, preferably at least 60 wt.% of a transition alumina-based material, and most preferably 70 wt.% of a transition alumina-based material.

[0024] The transition alumina-based material may have a specific surface area of 50 m 2 / g to 300 m 2 / g, and a pore volume of 0.1 ml / g to 1.5 ml / g.

[0025] The specific surface area provided herein is measured by BET using nitrogen according to DIN-ISO 9277. The pore volume and pore size distribution are measured using nitrogen adsorption at 77 K by the method proposed by Barrett, Joyner, and Halenda (BJH).

[0026] The rare earth phosphate is preferably LaPO4, YPO4, or NdPO4, and more preferably LaPO4.

[0027] According to one embodiment of the present invention, the composition comprises 3 to 50 wt.% of rare earth phosphate, preferably 10 to 30 wt.% of rare earth phosphate, more preferably 5 to 30 wt.% of rare earth phosphate, each calculated in the form of the corresponding rare earth oxide.

[0028] The rare earth phosphate preferably has a crystallite size of less than 15 nm after calcination at 1000 °C for 3 hours, and most preferably a crystallite size of less than 10 nm after calcination at 1000 °C for 3 hours.

[0029] The crystallite size is determined by the Scherrer method using the (21-2) reflection in the X-ray powder diffraction pattern of the composition (indexed based on the monoclinic monazite structure, ICSD reference code: 98-007-9747) after heat treatment in air at 1000 °C for 3 hours in the case of La and Nd phosphates, and using the (020) reflection in the X-ray powder diffraction pattern of the composition (indexed based on the tetragonal zircon structure, ICSD reference code: 98-002-4514) after heat treatment in air at 1000 °C for 3 hours in the case of Y phosphate.

[0030] The rare earth phosphates are preferably uniformly dispersed in the matrix of the transition alumina-based material. Without being bound by theory, the applicant believes that the uniform dispersion of small crystals of rare earth phosphates enables the transition alumina matrix to act as a diffusion barrier, thereby obtaining beneficial properties of the composite material. Homogeneity is measured by scanning electron microscopy (SEM) cross-sectional imaging, optionally together with EDX element mapping revealing the domain sizes of the transition alumina-based material and the rare earth phosphates.

[0031] The composition of the present invention preferably has a BET specific surface area of at least 50 m 2 / g, preferably 70 m 2 / g to 150 m 2 / g, and a pore volume of 0.2 ml / g to 1.2 ml / g, preferably 0.3 ml / g to 1.0 ml / g. These measurements are carried out as described above.

[0032] According to a second aspect of the present invention, there is provided a method for preparing a composition for use as a carrier in a catalyst system, the method comprising:

[0033] i) providing an alumina rare earth oxide material, wherein the transition alumina rare earth oxide material is prepared by a method comprising the steps of:

[0034] a) preparing a suspension comprising a transition alumina precursor;

[0035] b) preparing an aqueous solution comprising a rare earth salt;

[0036] c) combining the suspension with the rare earth salt solution to form an alumina rare earth salt mixture;

[0037] d) drying the alumina rare earth salt mixture to form a dried alumina rare earth salt mixture; and

[0038] e) calcining the dried alumina rare earth oxide salt mixture to form the transition alumina rare

[0039] earth oxide material;

[0040] ii) impregnating the alumina rare earth oxide material with an aqueous solution containing phosphate ions to form an impregnated alumina rare earth oxide material; and

[0041] iii) calcining the impregnated alumina rare earth oxide material.

[0042] The phosphate ions may comprise or in other words may be derived from phosphoric acid, orthophosphate, hydrogen phosphate, dihydrogen phosphate, diphosphate, triphosphate, metaphosphate, pentaphosphate, polyphosphate or mixtures thereof.

[0043] The transitional alumina precursor preferably comprises an alumina hydrate of the general formula Al(OH)3 and / or AlOOH*xH2O or a mixture thereof. The alumina precursor is preferably boehmite. The alumina precursor may further comprise silica, titanium dioxide, water-soluble salts of alkaline earth metals, zirconium or mixtures thereof. The alumina precursor preferably comprises at least 50 wt.% of an alumina hydrate of the general formula Al(OH)3 and AlOOH*xH2O or a mixture thereof.

[0044] The suspension containing the transitional alumina precursor is preferably a boehmite suspension prepared by hydrolysis of an aluminum alkoxide.

[0045] The suspension containing the transitional alumina precursor preferably comprises the alumina precursor and water in a ratio of at least 2:98 to 20:80. The suspension may further comprise a pH adjusting additive such as a carboxylic acid or ammonia, preferably a monocarboxylic acid such as acetic acid.

[0046] The rare earth salt is a water-soluble salt, preferably a rare earth acetate, more preferably lanthanum (La) acetate, yttrium (Y) acetate, neodymium (Nd) acetate or mixtures thereof, and more preferably lanthanum (La) acetate.

[0047] The rare earth salt solution preferably comprises a rare earth salt and water, corresponding to a rare earth oxide content of 2 to 20 wt.% in the solution. The suspension may further comprise a pH adjusting additive such as a carboxylic acid or ammonia.

[0048] The alumina rare earth salt mixture preferably comprises at least 50 wt.% of the transitional alumina precursor, preferably at least 60 wt.% of the transitional alumina precursor, and most preferably 70 wt.% of the transitional alumina precursor.

[0049] The alumina rare earth salt mixture preferably comprises 3 to 50 wt.% of the rare earth salt calculated as the corresponding rare earth oxide, preferably 10 to 30 wt.% of the rare earth salt, and more preferably 5 to 30 wt.% of the rare earth salt.

[0050] The alumina rare earth salt mixture is preferably spray-dried.

[0051] Then, the dried rare earth salt-aluminum oxide mixture is preferably calcined at a temperature of 450 to 1200 °C for a period of 0.5 to 5 hours to form a transition alumina rare earth oxide material.

[0052] The impregnation of the transition alumina rare earth oxide material can be carried out by any impregnation method known in the art. Preferably, the well-known incipient wetness impregnation method is used, preferably by filling 80 - 100% of the pore volume of the rare earth oxide-aluminum oxide material with an aqueous solution containing phosphate ions (preferably phosphoric acid). Preferably, this solution is used for impregnation up to an amount providing a molar ratio of phosphoric acid to rare earth element of 10 to 100 mol%. For example, if the rare earth element is La and if the ratio is 100 mol%, there is an equimolar amount of La and PO4 3- , and only LaPO4 is present on the transition alumina. If the ratio is 10 mol%, only 10 mol% of LaPO4 and 90 mol% of La in oxide form are present on the transition alumina.

[0053] Then, the impregnated transition alumina rare earth oxide material is preferably calcined at a temperature of 600 to 1100 °C, preferably at 900 to 1100 °C and most preferably 1000 °C. The calcination can be carried out for a period of 0.5 to 5 hours, preferably 3 hours.

[0054] The thermal stability of the composition according to the invention (and obtained from the method according to the invention) can be determined by calcining the composition at 1200 °C for 3 hours. After calcining the composition at 1200 °C for 3 hours, the composition is preferably characterized by one or more of the following:

[0055] - The BET specific surface area of the composition is at least 40 m 2 / g, preferably 45 m 2 / g to 90 m 2 / g;

[0056] - The pore volume of the composition is 0.3 ml / g to 1.0 ml / g, preferably 0.4 ml / g to 0.9 ml / g,

[0057] where the BET specific surface area and pore volume measurements are carried out as described above.

[0058] The present invention will now be described with reference to non-limiting examples and the accompanying drawings, in which:

[0059] Figure 1 is the powder XRD of the composition obtained in Example 1 compared to Comparative Example 1, showing the difference in the crystallinity of LaPO4;

[0060] Figure 2is the SEM of Example 1 and shows uniform white spots (the material of the present invention); and

[0061] Figure 3 is the SEM of Comparative Example 1 and shows white spots in a gray matrix, which means there are RE-rich regions (white regions) and Al-rich regions (gray regions).

[0062] Examples:

[0063] As described above, the crystallite size was determined by the Scherrer method.

[0064] As described above, the surface area was measured by BET and the pore volume was measured by N2 adsorption.

[0065] Experiments

[0066] Example 1

[0067] A transition alumina rare earth oxide material made of 20 wt.% lanthanum oxide was impregnated with an aqueous solution of phosphoric acid (14.4 wt.% H3PO4). The material contains transition alumina with a specific surface area (BET) of 130 m 2 / g and a pore volume of 0.97 ml / g. The product was dried at 120 °C and finally calcined at 1000 °C for 3 hours.

[0068] Example 2

[0069] A transition alumina rare earth oxide material made of 20 wt.% yttrium oxide was impregnated with an aqueous solution of phosphoric acid (13.2 wt.% H3PO4). The material contains transition alumina with a specific surface area (BET) of 134 m 2 / g and a pore volume of 0.98 ml / g. The product was dried at 120 °C and finally calcined at 1000 °C for 3 hours.

[0070] Example 3

[0071] A transition alumina rare earth oxide material made of 20 wt.% neodymium oxide was impregnated with an aqueous solution of phosphoric acid (14.4 wt.% H3PO4). The material contains transition alumina with a specific surface area (BET) of 130 m 2 / g and a pore volume of 0.97 ml / g. The product was dried at 120 °C and finally calcined at 1000 °C for 3 hours.

[0072] Example 4

[0073] A transition alumina rare earth oxide material made of 15 wt.% lanthanum oxide was impregnated with an aqueous solution of phosphoric acid (9.7 wt.% H3PO4). The material contains transition alumina with a specific surface area (BET) of 145 m 2Transition alumina with a specific surface area of 151 m² / g and a pore volume of 0.94 ml / g. The product was dried at 120 °C and finally calcined at 1000 °C for 3 hours.

[0074] Comparative Example 1

[0075] LaPO4 was prepared according to Example 3 of EP 2754489A1:

[0076] A phosphoric acid solution was added to a lanthanum nitrate solution in an amount to produce a 1:1 molar ratio of La and P. The pH value was adjusted to 8 by adding an ammonia solution. The precipitate was separated by filtration and finally calcined at 900 °C for 5 hours.

[0077] The obtained LaPO4 was combined with alumina. A slurry of LaPO4 powder and 4 wt.% lanthanum-doped alumina with a specific surface area (BET) of 151 m² / g and a pore volume of 1.02 ml / g was prepared and wet-milled. Then the suspension was spray-dried and calcined at 1000 °C for 3 hours to obtain a comparative composite material. 2 / / g and a pore volume of 1.02 ml / g was made into a slurry and wet-milled. Then the suspension was spray-dried and calcined at 1000 °C for 3 hours to obtain a comparative composite material.

[0078] Comparative Example 2

[0079] According to Example 6 of GB 1431868, CePO4 was prepared by using commercially available PURALOX TH100 / 150 to evaporate (NH4)2Ce(NO3)6 on alumina and heating it overnight to 400 °C. Then, phosphoric acid was added to the cooled mixture. After calcining at 1000 °C for 3 hours, the comparative product was tested and no CePO4 was found; only AlPO4 was found. The specific surface area (BET) of the comparative product was 45 m² / g. 2 / g.

[0080] The results are included in Table 1 below:

[0081] Table 1:

[0082]

[0083] * As received

[0084] ** After additional calcination at 1200 °C for 3 h (for thermal stability)

[0085] Figure 1 XRD patterns of the materials obtained in Example 1 and Comparative Example 1 are shown. The difference in the crystallinity of LaPO4 is clearly shown by the width of the diffraction lines. Table 1 lists the values extracted by the Scherrer method.

[0086] In addition, Figure 2 and Figure 3 The SEM cross-sectional views in show Example 1 ( Figure 2 ) and Comparative Example 1 (Figure 3 ) The materials obtained therein. It should be noted that the difference in the uniformity of the two samples appears as well-defined white spots (corresponding to regions rich in LaPO4), indicating lower uniformity.

Claims

1. A composition used as a carrier in a catalyst system in an emission control system, comprising: i) a transition alumina-based material; and ii) a rare earth phosphate, characterized in that it has a crystallite size of less than 15 nm after calcination at 1000 °C for 3 hours, and the rare earth phosphate includes LaPO4, YPO4, NdPO4, or a mixture thereof.

2. The composition according to claim 1, wherein the transition alumina-based material includes transition alumina derived from boehmite, silica-alumina, doped alumina, or a mixture thereof.

3. The composition according to claim 1 or claim 2, comprising at least 50 wt.%, preferably at least 70 wt.%, of the transition alumina-based material.

4. The composition according to any one of claims 1 to 3, comprising 3 to 50 wt.% of the rare earth phosphate, preferably 10 to 30 wt.% of the rare earth phosphate.

5. The composition according to any one of claims 1 to 4, wherein after calcination at 1000 °C for 3 hours, the rare earth phosphate has a crystallite size of less than 10 nm.

6. The composition according to any one of claims 1 to 5, having a BET specific surface area of at least 50 m 2 / g, preferably 70 to 150 m 2 / g.

7. The composition according to any one of claims 1 to 6, having a pore volume of 0.2 to 1.2 ml / g, preferably 0.3 to 1.0 ml / g.

Citation Information

Patent Citations

  • Catalyst carrier for exhaust gas purification and catalyst for exhaust gas purification

    EP2754489A1

  • Catalytic oxydehydrogenation of alkyl aromatic compounds

    GB1431868A